Ecological-Economic Efficiency Of Use Of Land In Agriculture Of The Bryansk Region In The New Socio-Economic Conditions - Dolganova M.V. (Научно-технический вестник Брянского государственного университета)
The article assesses the ecological and economic efficiency of use of agricultural land in the Bryansk region in the new socio-economic conditions, summarizes the dynamics of the area of agricultural land, utilization of land resources for a number of years. The article substantiates the main directions for further enhancing the efficiency of land resources of the Bryansk region in the conditions of the market.